Konvergensi Metode Elemen Hingga Polygonal Hibrid dalam Analisis Kristal Fotonik 2D - Eny Sukani Rahayu; Samiadji Herdjunanto (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2012)
Finite element method (FEM) with hybrid polygonal elements using Wachspress shape functions to analyzethe band gap characteristic of two-dimensional photonic crystals (2D PCs) is presented in this paper. Hybrid polygonal elements are mix elements between polygonal (n>3) and triangular elements. In triangular elements, Wachspress shape function is linear while in polygonal elements, the shape function becomes high order. The performance of the method compared with which of the linear triangular FEM is presented in its convergence rate graph showing the trend of accuracy. The flexibility in meshing using polygonal elements with Wachspress shape function as the interpolation function is also presented. The results show that hybrid polygonal FEM gives better accuracy compared with linear triangular FEM.